(3eLGdS hbUU (B( (3RgQ GdceGe aj bUI jhSa Ydjg GdSdGe (B)s
(3ChdgG (B:s
(3GdeLdS GdChd (B: (3ai bhdg JYGdi (B: ( (3hbVi QHc CdG JYHOhG EdG ZjGg hHGdhGdOjf EMSGfkG (B) s
(3BNQgG (B:s
(3aLfGHg QMH dcd eDed hgh GdEdg GdhGMO GdbgGQ Je cJGH RgQ GdceGe ai bUI jhSa Ydjg GdSdGe HJGQjN GdYTQjf ef TgQ UaQ GdNjQ ef TghQ SfI EKfjf hSJjf hKeGfeGFI s
(3HgG fXGe GdJYbjHIs
(3SaQ jVe SHYI YTQ eLdSkG ai eYfi ef eYGfi HYV GdBjGJ GdcQjeI jJNddgG TF ef GdTYQ hGdbUU hGdCNHGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJaSjQ hYdhe GdbQBfs